The Right to Historical Truth and Modern Narrations - Tsulukidze, Mari; Totadze, Lela (Vilnius University Open Series, 2024)
Presented research paper analyzes the right to truth, its scope within the modern legal system and its protection within different storytelling practices. As it is discussed in the paper modern narrations tend to avoid past and try to hide some uncomfortable or shameful aspects of history which at some point breaches the right to historical truth therefore there is an ongoing discussion that the scope of the right to truth should be broader and it should be considered as a collective right of groups to have the access to truth about historical aspects.During the work on this topic, it became clear that the “artistic license” which allows artists to be free to choose the methods or ways to portray some historical aspects may at some point breach the right to historical truth and conveying the altered historical facts sometimes affect the way people view current reality or make important choices.Presented research also discusses the book banning process in the US school systems which resulted in removing many widely famous books from the library shelves. Based on the research, the US Supreme court’s comments can be considered agreeable. In particular, putting an end to racial discrimination should be achieved by other proper solutions rather than book banning methods. As it is mentioned in the research, access to information is essential for developing critical thinking and it is closely related to the right to truth of individuals.This article also discusses some psychological research and analyzes how the alteration of facts influence the vision and future choices of individuals. Mentioned examples also underline the importance of the right to historical truth and access to accurate historical aspects.Based on the research, it can be assumed that the right to truth should protect broader areas of individual’s lives since the access to accurate past events at some point ensure the development of critical thinking of individuals and may guarantee that members of society will take right steps regarding the modern political or social situations.